The Influence of Three Forms of Collaboration on the Performance of Food SMEs in Indonesia - Hadi, Suryadi; Dwiwijaya, Kadek Agus; Murad, Mohammad Ali; Anjany, Ni Luh Verha; Hendra, Syaiful; Ngemba, Hajra Rasmita (Universitas Brawijaya, Indonesia, 2025)
The increasing complexity of supply chains, driven by globalization and technological advancements, necessitates effective logistics collaboration, particularly for food SMEs in Indonesia. Despite its recognized benefits, many SMEs face fragmented supply chains, inefficient distribution networks, and resource limitations that hinder competitiveness. Addressing these challenges is crucial for improving supply chain resilience and efficiency. This study examines the influence of horizontal, vertical, and lateral logistics collaboration on the supply chain performance of food SMEs in Indonesia. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), the study analyzes data from food SMEs in Palu, Indonesia. A purposive sampling technique was employed, targeting SME owners and managers involved in logistics collaboration, resulting in a final sample size of 92 respondents. The findings reveal that horizontal logistics collaboration has the most significant impact, enhancing efficiency and effectiveness through partnerships among SMEs and distributors. Vertical collaboration also demonstrates a strong influence, improving integration and synchronization between producers and distributors. However, lateral logistics collaboration does not exhibit a statistically significant effect, likely due to coordination challenges and a lack of resources. This study contributes to logistics literature by empirically validating the varying impacts of collaboration types on SMEs' supply chains in an emerging market. The findings highlight the superior role of horizontal partnerships and suggest fostering collaboration through digital platforms, training, and the adoption of technology. Future studies should explore government policies, digitalization, and sustainability practices to develop comprehensive strategies for optimizing logistics collaboration among SMEs.